TURKESTAN COLLECTION AS A VALUABLE DOCUMENTARY SOURCE ON THE HISTORY OF COLONIAL TURKESTAN - Akhmedzhanov Azimjon Marufovich (Scholar Express Journal, 2024)
Turkestan collection of essays and articles relating to Central Asia in general and the Turkestan region in particular” is a collection of various printed materials (books, magazine and newspaper articles, newspaper clippings and magazines) on various topics relating to the Central Asian possessions of the Russian Empire. The compilation of the collection was started at the suggestion of the Turkestan Governor-General K.P.Kaufman in order to provide information to representatives of the Russian administration and the intellectual community regarding the situation in various areas of life in the newly annexed region. The appearance of the “Turkestan Collection” marks an important stage in the comprehensive study of Central Asia during the period of its annexation to the Russian Empire. This article provides information on the use of the Turkestan collection as a valuable documentary source for the history of Colonial Turkestan
Keywords: Turkestan collection; Colonial Turkestan; Central Asian possessions